Comparison of Various Techniques for Load Balancing in Cloud Computing - Gond, Sunita; Singh, Shailendra (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is innovative technology that provide various applications and services to users. Cloud services are offered to user on the basis of utility, users have to pay only that amount for which they have used the services. Many challenges are there for cloud computing include virtual machine migration strategy fault tolerance, availability, scalability, load balancing and security. An optimal solution for load balancing is to manage proper resource utilization, minimum consumption of resources, minimum fail over, proper scaling etc[1]. Static load balancing algorithm does not adaptive quality of load balancing at run time while dynamic load balancing work dynamically at run time for better result. All nodes with its details properties are required in advance to handle traffic load balancing. Software requires for operating, handling, and integrating the services of various applications over the cloud. Comparison of static and dynamic load balancing done on various parameters analyzed in this paper that includes overhead incurred, support fault tolerance, proper resource management, scalable property etc.